2019
DOI: 10.3390/jcm8060771
|View full text |Cite
|
Sign up to set email alerts
|

An In Vitro Study of Osteoblast Response on Fused-Filament Fabrication 3D Printed PEEK for Dental and Cranio-Maxillofacial Implants

Abstract: Polyetheretherketone (PEEK) is a prime candidate to replace metallic implants and prostheses in orthopedic, spine and cranio-maxillofacial surgeries. Fused-filament fabrication (FFF) is an economical and efficient three-dimensional (3D) printing method to fabricate PEEK implants. However, studies pertaining to the bioactivity of FFF 3D printed PEEK are still lacking. In this study, FFF 3D printed PEEK samples were fabricated and modified with polishing and grit-blasting (three alumina sizes: 50, 120, and 250 µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 36 publications
1
62
0
2
Order By: Relevance
“…In the field of dentistry, the possibility of computer-aided design/computer-aided manufacturing (CAD/CAM) together with its biocompatibility and shock absorbing features [10,16,17] has enabled the increased use of PEEK. These uses were extended to the fabrication of a considerable number of materials including healing caps, abutments, removable prostheses, crowns, fixed or partial full-arch dentures, and dental implants [10][11][12][13][14][15][18][19][20][21][22][23]. Despite the scarce in vivo publications, PEEK was demonstrated to be a valid treatment option compared to titanium in the rehabilitation of severely atrophic maxillary alveolar ridges both through patient-specific sub-periosteal implants [24] and as a customized mesh for bone augmentation [25].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of dentistry, the possibility of computer-aided design/computer-aided manufacturing (CAD/CAM) together with its biocompatibility and shock absorbing features [10,16,17] has enabled the increased use of PEEK. These uses were extended to the fabrication of a considerable number of materials including healing caps, abutments, removable prostheses, crowns, fixed or partial full-arch dentures, and dental implants [10][11][12][13][14][15][18][19][20][21][22][23]. Despite the scarce in vivo publications, PEEK was demonstrated to be a valid treatment option compared to titanium in the rehabilitation of severely atrophic maxillary alveolar ridges both through patient-specific sub-periosteal implants [24] and as a customized mesh for bone augmentation [25].…”
Section: Introductionmentioning
confidence: 99%
“…Most clinically used patient-specific implants for oral and maxillofacial reconstruction are composed of titanium, poly-ether-ether-ketone (PEEK), and other non-absorbable materials [ 6 , 8 , 9 ]. However, to achieve optimal scaffolding to facilitate regeneration of hard tissues, various scaffold properties, such as controlled biodegradability, architecture, mechanical property, biocompatibility, and osteoconductivity, should be considered.…”
Section: Introductionmentioning
confidence: 99%
“…PEEK has been used in cranioplasty as a reliable alternative to other alloplastic materials [ 23 , 24 ]. Previous studies have shown the possibility of printing PEEK by FFF [ 17 , 25 , 26 ]; however, studies on FFF 3D printed PEEK cranial implants are limited. Therefore, to investigate the outcome of quality and clinical relevance of FFF 3D printing technology at POC manufacturing, the present study was conducted.…”
Section: Discussionmentioning
confidence: 99%